Neutralisation of Non-Standard Language in Literary Translation and Its Influence in the Character’s Image, a Cognitive Perspective - Dziekan, Katarzyna (2024)
Neutralisation is a recurrent translation strategy. When applied to a literary translation, neutralisation poses a threat to a literary character’s authenticity. The subject of the research is the influence of the literary character’s idiolect on the character’s image created in the text, as well as the consequences of neutralisation of non-standard language spoken by the character in translation. The problem is approached from the point of view of cognitive linguistics and cognitive poetics. The applied methodology draws on the dimensions of construal, differentiated within cognitive grammar. The paper is based on the analysis of the Polish novel Wojna-polsko ruska pod flagą biało-czerwoną by Dorota Masłowska and its Spanish and English translations. It has been found that non-standard language spoken by the protagonist concerns different dimensions of construal, and neutralisation of the language has an impact on them. The research indicates the utility of cognitive methodology in the study of language variation in literary translation.
Keywords: literary translation; non-standard; language variation; neutralisation; cognitive linguistics; idiolect; characterisation